1990
DOI: 10.1086/132667
|View full text |Cite
|
Sign up to set email alerts
|

Massa's star, HD 93840 - A new extreme BN supergiant

Abstract: New optical digital spectrograms of HD 93840 and several comparison objects are presented and discussed, together with IUE high-resolution data for the same stars. The optical observations confirm HD 93840 (BN1 lb) as an extreme nitrogen-enhanced supergiant, as originally suggested by Massa on the basis of the UV stellar-wind profiles alone. The contrasts with HD 96248 (BC1.5 lab) are especially striking. The rich UV stellar-wind phenomenology of these objects is discussed in some detail; there is a suggestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…N v is heavily saturated in the O3 object, while all O5 stars show a nonsaturated profile. This is in agreement with the spectrum of HD 14 947 displayed by Walborn et al (1985), although it does not agree with the newly reduced spectrum contained in the Final IUE Archive. The line weakens towards later spectral types and is no longer visible at B1.…”
Section: Description Of the Spectrasupporting
confidence: 42%
“…N v is heavily saturated in the O3 object, while all O5 stars show a nonsaturated profile. This is in agreement with the spectrum of HD 14 947 displayed by Walborn et al (1985), although it does not agree with the newly reduced spectrum contained in the Final IUE Archive. The line weakens towards later spectral types and is no longer visible at B1.…”
Section: Description Of the Spectrasupporting
confidence: 42%
“…Morton (1979) concluded that there is no O vi in p Leonis and implied that its absence, although a strong N v wind profile is present, may be a critical ionization effect. However, p Leo is moderately nitrogen enhanced, and its Nv profile is anomalously strong compared with other B1 supergiants (Walbom et al 1990; B Atlas), so its O vi vs. N v discrepancy may also be partly a chemical abundance effect.…”
Section: Late-o Supergiantsmentioning
confidence: 94%
“…We compare the WR 140 WC7pd+O4-5 IUE spectrum with that of the single WC star WR 90 in Willis et al (1986), and with those of single O4-5 stars presented in Walborn et al (1985). We measured the equivalent widths of absorption and emission parts of the P-Cygni profiles at around 1400Å (Si iv) and 1720Å (N iv), and list them in Table 3.…”
Section: The Luminosity Of the O Componentmentioning
confidence: 99%